Development and performance evaluation of a low-cost paper egg tray making machine (2022)
Chicken eggs are extremely fragile and require protective packaging for handling, storage and delivery. Paper egg tray, the most globally acceptable package for eggs, is often im- ported, costly and scarce in Nigeria due to difficulties in procurement and management of standard machines for trays’ local production. Therefore, this study was intended to lo- cally develop and evaluate the performance of a low-cost paper egg tray-making machine to ease the local production and distribution of paper egg trays in Nigeria. Using metal scraps as construction materials and a sand-casting method for mould manufacture, a 30- cell paper egg tray-making machine was developed, and its performance was evaluated. Power rating determination of the machine was done using Logger Interface Program. The paper egg trays having dimensions of 300 ×300mm; cell diameter of 35mm; cell depth of 25mm; and wet and dry weights of 298.0 g and 86.0 g, respectively, were produced. The vibration resistance of the manufactured trays was compared with existing oness at a frequency of 5 Hz. The machine of 1.4 Kw power rating and sand-cast aluminum-alloy moulds was developed at a total cost of N76, 720 ($210). The machine could be oper- ated manually with a minimum of one employee, using reciprocating mould movement at a capacity of ten trays per hour. An acceptable paper egg tray was obtained with Chip- board (65.0%) and Newsprint (35.0%) wastepaper mix, fabric-mesh hole-size of ≤0.6 mm and pulp slurry of 4.0% consistency. The vibration resistance result showed that the egg failure by the manufactured and existing paper egg trays was moderate and comparable. The machine development could encourage waste management, youth employment, and affordable local paper egg tray manufacture and supply in Nigeria.